The origins of vowel systems - De Boer, Bart (Studies in the evolution of language, 2001)
"This book addresses the question of how the properties of human vowel systems can be explained. Though vowel systems of human languages are optimal for communicative purposes, it is not clear who is doing the optimization. If children learn a language, they learn to produce sounds that are as close as possible to those used by their parents and peers. The author argues that the optimization is the result of self-organization in a population of language users. Self-organization is the emergence of order on a global scale in a system where there are only local interactions. It is a phenomenon that appears in many natural systems from purely physical ones, such as crystals, to systems composed of living organisms, such as colonies of insects. Recent developments in linguistics indicate that self-organization might also play an important role in language."--BOOK JACKET.